Perception and Effects of Dramas on University Students - Jawaria Latif; Subha Malik; Madiha Nadeem (National University of Modern Languages (NUML), Islamabad, 2021)
Drama as an important mean of the media can impact the lives of people and consequently influence the whole society. This study conducted to understand the perception of students and the effects of Hum TV dramas on university students of Lahore. For this, mixed method research design was applied. Focus groups and self-constructed questionnaire were used for data collection from conveniently selected male and female students of public and private universities. Qualitative results revealed that subject selection and features of dramas determined the students' attitude towards watching trends. Similarly, the perceived impact of dramas on culture, lifestyles, fashion sense and even on spouse selection criteria were reported by both male and female students. Quantitative results did not show any significant gender difference in the subject preference of dramas, features and impacts of dramas. Moreover, subject selection and features of dramas for watching differed with students' year of study.